An annotated synopsis of Taiwanese bark and ambrosia beetles, with new synonymy, new combinations and new records (Coleoptera: Curculionidae: Scolytinae) - Beaver, R. A.; Liu, L. Y. (Zootaxa, 2010)
The state of knowledge of Taiwanese bark and ambrosia beetles (Coleoptera: Curculionidae: Scolytinae) is summarised to serve as a baseline for future studies of the fauna, with a checklist including information on distribution, host trees, biology and taxonomy. Six faunal elements based on geographical distribution are discussed in relation to their breeding sites and habits, and host preferences. One hundred and thirty-three species are recorded from Taiwan, of which thirtyeight are recorded for the first time. The following new synonymy is proposed: Ambrosiodmus lewisi (Blandford) (= Ozopemon tuberculatus Strohmeyer n. syn.), Anisandrus hirtus (Hagedorn) (= Xyleborus taiwanensis Browne n. syn.), Cyclorhipidion fukiensis (Eggers) (= Xyleborus tenuigraphus Schedl n. syn.), Cyrtogenius luteus (Blandford) (=Orosiotes formosanus Schedl n. syn.), Diuncus haberkorni (Eggers) (=Xyleborus taichuensis Schedl n. syn.) , Dryocoetes hectographus Reitter (=Ozopemon ater Eggers n. syn., =Dryocoetes formosanus Nobuchi n. syn.), Hypothenemus taihokuensis (Schedl) (=Hypothenemus cosmoderoides Murayama n. syn.), Xyleborinus artestriatus (Eichhoff) (= Xyleborus beaveri Browne n. syn.), Xyleborus pinicola Eggers (= Xyleborus pinivorus Browne n. syn.). The synonymy of Webbia camphorae Eggers and Webbia medius Eggers with Arixyleborus rugosipes Hopkins is confirmed. The following new combinations are given: Ernoporus formosanus (Browne) from Ptilopodius Hopkins; Ambrosiophilus hunanensis (Browne), A.metanepotulus (Eggers), A. satoi (Schedl), A. subnepotulus (Eggers), Cyclorhipidion formosanus (Browne), C. fukiensis (Eggers), C. ohnoi (Browne), C. xyloteroides (Schedl), Microperus kirishimanus (Murayama), Planiculus minutus (Blandford), all originally described in Xyleborus Eichhoff. Previous records of 23 species are considered dubious and require confirmation.